Rancang Bangun Generator Fluks Aksial Putaran Rendah Magnet Permanen Jenis Neodymium (NdFeB) Untuk Turbin Angin Sumbu Vertikal Tipe Double-Stage Savonius - Mohammad Fiky Alqodri; Cecep E. Rustana; Hadi Nasbey (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Axial flux generator is a simple generator that is able to work at low rpm. This generator consists of a stator and rotor parts, parts stator consists of a coil of copper wire arranged to form three-phase, and part of the rotor consists of a permanent magnet type Neodymium (NdFeB) permanent magnet has a magnetization value (remanent) large enough so that it can produce magnetic flux is big enough. The axial flux generator is suitable for wind turbines savonius which can rotate at low wind speeds. The design of the generator and installation of the turbines is needed to minimize costs, increase torque, moving on some variation of wind speed is low. To increase the power output of the system, then the doubling generator that will be installed on the turbine. Expected by installing generators axial flux permanent magnet type NdFeB and increasing the number of generators in the turbine, can further improve the efficiency of the system. at low wind speed produce voltage and current 0,079 V, 0,079 A at 17,2 rpm and 2 V, 0,354 A at 500 rpm. Keywords: axial flux generator, a permanent magnet. efficiency of the system.